WEATHER TYPES IN THE NORWEGIAN ARCTIC - Araźny, Andrzej (Bulletin of Geography. Physical Geography Series, 2009)
In order to assess the usefulness of Norwegian Arctic bioclimatic conditions for outdoor activities in the years 1971–2000, the author applied his own weather typology developed on the basis of the classification proposed by Błażejczyk (1979). The typology classified four weather groups for the study area. Atmospheric circulation types proposed by Niedźwiedź (2002) were used to determine the synoptic situations and types of favourable weather conditions for outdoor recreation, tourism and work, as well as those that may pose a threat to human life.